Mother’s level of education and attitude determines the provision of complete basic immunization in infants - Risna Ayu Rahmadani; Yuliati Lumintang; Ike FA Chabibah (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2025)
Introduction: Immunization is an effort to introduce vaccines into the body to increase a person's immunity and prevent a disease. The impact or risk of incomplete immunization is that children are more susceptible to illness, are at more risk of infecting family members or the environment, and the quality of life and life expectancy decrease. During the research, data were found that 19 out of 35 infants did not receive complete immunization. This research aimed to determine the relationship between the mother’s education level and attitude towards providing complete basic immunization in infants at the Tombatu Community Health Center, Winorangian Satu Village. Methods: Partial analytical observational research with a cross-sectional design, with independent and dependent variables, was conducted simultaneously with a sample size of 35 respondents. The analysis method used is the Chi-square. Result: The mother's education level was higher in the high category (>junior high school), and the mother's attitude was associated with a frequency of 19 respondents (not supporting <50%). The Chi-square test results showed a relationship between maternal education level and the provision of complete basic immunization in infants at the Tombatu Community Health Center, Winorangian One Village, p-value = 0.00. The Chi-square test results showed a relationship between maternal attitudes and the provision of complete basic immunization in infants at the Tombatu Community Health Center, Winorangian Village. One p-value = 0.00. Conclusion: The study results found a relationship between the mother’s level of education and the provision of complete basic immunization to babies at the Tombatu Community Health Center. Winorangian Satu Village, and there is a relationship between the mother's attitude and the provision of complete basic immunization in infants at the Tombatu Community Health Center, Winorangian Satu Village